Impact of Tansmigration Development UPT.Waleh SP.2 on Carbon Emissions - Utdin Furqon Amali; Sherly Asriany; Mohamad Jamil (Jurnal Ilmiah Multidisiplin, 2025)
This article is the result of a research on the impact evaluation of transmigration development on carbon emissions in UPT Waleh SP.2, Central Halmahera Regency, North Maluku. Where the opening of transmigration land has the potential to change ecosystems, including vegetation cover, biomass, and greenhouse gas emissions, which can affect environmental sustainability. The objective of this study was to analyze changes in the ecosystem due to transmigration development, particularly on vegetation cover, carbon biomass, and carbon emissions. For this purpose, remote sensing technology and GIS-based spatial analysis were used with four main indicators: NDVI for vegetation cover, AGB for carbon biomass, CO as an emission indicator, and NPP for carbon absorption capacity. The results showed a decrease in NDVI, AGB, and NPP, as well as an increase in CO. Decreases in NDVI and AGB reflect vegetation degradation and biomass loss, while increases in CO are caused by human activities such as biomass burning and the use of motorized vehicles. The decrease in NPP indicates a decrease in the capacity of vegetation to absorb carbon.